2007
DOI: 10.4067/s0365-28072007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Utilización de Microsatélites para la Determinación de la Polilla de la Manzana Cydia pomonella L. (Lepidoptera: Tortricidae) en Chile Central

Abstract: A B S T R A C TCodling moth (Cydia pomonella L.) is the main pest of pip fruits worldwide. Despite its economic importance, little is known about the genetic structure and patterns of movement at local and regional scale, important aspects for establishing a control strategy for this pest. An analysis of genetic variability on six populations of C. pomonella using microsatellite was performed in the two major apple (Malus domestica Borkh.) growing regions of Central Chile. In spite of geographic distances betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
(29 reference statements)
0
7
1
Order By: Relevance
“…We found significant but low levels of genetic differentiation between codling moth populations from different localities and regions. Interestingly, the genetic differentiation between localities found herein (FST = 0.03) was one to two orders of magnitude higher than in previous studies of codling moth in Chile (FST = 0.002 − 0.0001), covering a more restricted latitudinal range of approximately 180 km and using only apples as the host plant [14,31]. It is important to note that microsatellite markers used herein were different to those used in the previous studies from Chile.…”
Section: Discussioncontrasting
confidence: 69%
“…We found significant but low levels of genetic differentiation between codling moth populations from different localities and regions. Interestingly, the genetic differentiation between localities found herein (FST = 0.03) was one to two orders of magnitude higher than in previous studies of codling moth in Chile (FST = 0.002 − 0.0001), covering a more restricted latitudinal range of approximately 180 km and using only apples as the host plant [14,31]. It is important to note that microsatellite markers used herein were different to those used in the previous studies from Chile.…”
Section: Discussioncontrasting
confidence: 69%
“…More likely, insecticide resistance in C. pomonella is affected by local conditions influencing selection pressure, the spatial distribution of managed and unmanaged hosts, and population movement between habitats. Several recent genetic studies of C. pomonella populations have shown that these factors can create widely different geographical patterns within France (Franck et al , 2007), Chile (Espinoza et al , 2007) and South Africa (Timm et al , 2006). However, within all geographical regions, effective efforts to combat resistance will require continuous monitoring of resistance mechanisms and the implementation of resistance management practices by both growers and the insecticide industry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent microsatellite DNA analysis on samples from different countries suggests that C. pomonella populations are structured according to geographical distance at supranational scale and that the intensity of insecticide applications is the main force structuring the populations at the national level (Franck et al, 2007). In the same way, Espinoza et al (2007) and Fuentes-Contreras et al (2008) did not detect differentiation by distance between Chilean C. pomonella populations, even when they were separated by more than 180 km. In contrast, Timm et al (2006) detected geographical differentiation in South-African populations.…”
Section: Introductionmentioning
confidence: 95%
“…Isolation of SSR markers in Lepidoptera has been shown to be particularly difficult due to similarities of regions flanking microsatellite loci or due to a multiplication of microsatellite loci as a consequence of the presence of mobile genetic elements (Meglécz et al, 2004(Meglécz et al, , 2007Zhang, 2004;Sinama et al, 2011). In addition, high null-allele frequencies and heterozygote deficits have been reported in many studies on SSR markers in Lepidoptera including L. botrana in the past (Amsellem et al, 2003;Ji et al, 2003;Franck et al, 2005;Van't Hof et al, 2005;Espinoza et al, 2007;Sinama et al, 2011). Presence of null-alleles may overestimate population differentiation and might hamper cross-species but also cross-population transferability and thus application of these markers in population genetic studies (Chapuis & Estoup, 2007).…”
Section: Discussionmentioning
confidence: 99%